Effectiveness of Smallholder Farmers adaptation to climate extremes: Evidence from the Southern Province of Zambia - Sichoongwe, Kiru; JinxiaWang (Agricultural Science, 2023)
Climate extreme is one of Zambia's most pressing issues impacting socio-economic development. This paper assessed the impact of adaptation to climate extremes, as well as the effectiveness of adaptation strategies to mitigate the negative impact on food production. A total of 270 smallholder farmers were sampled. Descriptive analysis, and, the   endogenous switching regression model were applied. According to the study's findings, adaptors and non-adaptors have a number of different characteristics. Furthermore, based on the estimates of the endogenous switching regression model, radio ownership, seed quantity and farming experience, had a positive relationship with adaptation. Also, the results showed that adaptors are ‘better producers’ than the non-adaptors. In light of the findings, some policy recommendations were made. When drafting policies (a) it is necessary to draw on the expertise and experience of farmers and local institutions, (b) consider the assets of the farmers and (c) enhance farmers’ access to more affordable agricultural inputs.